“Make A Match Model” for Improving the Understanding of Concepts and Student Learning Results - Ana Juliani; Ali Mustadi; Intan Lisnawati (Universitas Muhammadiyah Surakarta, 2021)
This study applies the “Make A Match model” to mathematics subjects, in increasing the ability to understand concepts and student learning outcomes in mathematics. This type of research is Classroom Action Research (CAR) and uses a Kemmis and Taggart model design with four stages, namely 1) Planning, 2) Action, 3) Observation, and 4) Reflection with a qualitative approach. This study uses 3 cycles, namely pre-cycle, cycle I and cycle II. Each cycle consists of four stages, namely: planning, action, observation, and reflection. This research was conducted at Yogyakarta PGRI University. The research subjects are second-semester students majoring in Elementary education (Pendidikan Guru Sekolah Dasar, hereafter called “PGSD”). The instrument used was a test that contained questions in the form of essays. Analysis of the data used is qualitative descriptive analysis. The results were obtained based on indicators of concept understanding, namely in the second cycle which increased including 1) students who were able to restate the concept from 62.50% in the pre-cycle to 76.38% in the second cycle, 2) students who were able to give examples 72.76% in the pre-cycle to 76.38% in the second cycle, 3) students who are able to present concepts in various representations from 70.86% in the pre-cycle to 85.34% in the second cycle, and 4) students who are able to associate internal or external Make A Match model from 70.69% pre-cycle to 76.38% in cycle II. It was concluded that the “Make A Match learning model” can improve students' understanding of concepts and learning outcomes in mathematics learning.